Exploring The Role of Employee Brand Ambassadors in Enhancing Brand Awareness and Customer Loyalty in Marketing Firms in Indonesia - Wijayanti, Tri Cicik; Ernawati, Riris (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to explore the role of employee brand ambassadors in enhancing brand awareness and customer loyalty in marketing firms in Indonesia. The study adopts a qualitative research design and utilizes semi-structured interviews as the primary data collection method. The research participants consisted of 15 HR managers from various marketing firms in Indonesia and 10 current or past employee brand ambassadors from those firms, selected using purposive sampling. They are selected based on their strong connection to the company’s mission and values, personal interest in the product or services offered, and desire to build a personal brand. The data collected from the interviews were analyzed using qualitative data analysis techniques, specifically through a thematic analysis approach. The data analysis process involved the identification of patterns, themes, and key ideas related to the research questions and objectives. The data analysis was an iterative process, with constant comparison and refinement of the categories to ensure the accuracy and validity of the findings. The findings reveal that employee brand ambassadors play a significant role in enhancing brand awareness and customer loyalty. They are selected based on their strong connection to the company’s mission and values, personal interest in the product or services offered, and desire to build a personal brand. They are trained to use a variety of strategies to promote the company’s brand and product or services, including social media, word-of-mouth marketing, attending events, and creating content. The study also highlights the impact of being a brand ambassador on the relationship between the employee and their company, as well as their colleagues. It increases employee engagement, boosts team morale, and improves overall communication. The impact of employee brand ambassadors is measured through metrics such as social media engagement, website traffic, and customer feedback. the study concludes that employee brand ambassadors are an effective way to enhance brand awareness and customer loyalty in marketing firms in Indonesia.